2016
DOI: 10.1108/jea-08-2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting instructional and transformational leadership

Abstract: Purpose – The purpose of this paper is to examine whether the taxonomy of two conceptual models of leadership roles for principals – instructional and transformational leadership (IL and TL) – can be traced empirically in a sample of Norwegian school leaders. Design/methodology/approach – The participants consisted of 149 school leaders attending a national training program for newly appointed principals at the University of Oslo. Leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Instructional leadership is defined as centred around the school principal (Aas & Brandmo, 2016;Nedelcu, 2013). It can be characterised as a top-down approach to school leadership because it mainly focuses on the principal and their tasks in coordinating and controlling instruction (Aas & Brandmo, 2016).…”
Section: Early Theories On Leadership In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instructional leadership is defined as centred around the school principal (Aas & Brandmo, 2016;Nedelcu, 2013). It can be characterised as a top-down approach to school leadership because it mainly focuses on the principal and their tasks in coordinating and controlling instruction (Aas & Brandmo, 2016).…”
Section: Early Theories On Leadership In Educationmentioning
confidence: 99%
“…Instructional leadership is defined as centred around the school principal (Aas & Brandmo, 2016;Nedelcu, 2013). It can be characterised as a top-down approach to school leadership because it mainly focuses on the principal and their tasks in coordinating and controlling instruction (Aas & Brandmo, 2016). Nedelcu (2013) states that Hallinger sees instructional leaders as hands-on principals, strongly focusing on the curriculum and unafraid of working with teachers on the improvement of teaching and learning.…”
Section: Early Theories On Leadership In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of leadership as a process where the leader is related to the situation and the followers, can therefore be helpful to create a more nuanced picture of school leadership in these dynamic low-and underperforming schools. In an examination of whether the taxonomy of two conceptual models of leadership roles for principals -instructional and transformational leadership -could be revealed empirically in a sample of Norwegian school leaders, Aas and Brandmo (2016) suggested that although the concepts of instructional and transformational leadership can be valuable for analytic reflections, they are too simplistic to represent the reality of school leaders' thoughts and actions. This means that the leader and their personal prerequisites must be related to the context in which they lead.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The opposite is more typically the case, as studies of school principals' leadership orientations in the Nordic cultural context suggest that international models, such as transformational leadership (Leithwood & Jantzi, 2000) and instructional leadership (Robinson, Lloyd, & Rowe, 2008), do not paint the full picture. For example, in a sample of Norwegian school principals, norms of democratic and distributed leadership were strong additional components in the school leaders' preference structure (Aas & Brandmo, 2016). Thus the current paper aims to contribute to Nordic school leadership research by exploring how school leaders operating in a challenging socioeconomic intake context over time work systemically with schools' internal and external determinants of school improvement.…”
Section: Introductionmentioning
confidence: 99%